Embodied Metarepresentations - Hinrichs, Nicolás; Foradi, Maryam; Yousef, Tariq; Hartmann, Elisa; Triesch, Susanne; Kaßel, Jan; Pein, Johannes (Frontiers in Neurorobotics, 2022)
Meaning has been established pervasively as a central concept throughout the disciplines that were involved in the cognitive revolution. Its metaphoric usage comes to be, first and foremost, through the interpreter’s constraint: representational relationships and contents are considered to be in the “eye” or mind of the observer and the shared properties between observers themselves are knowable through interlinguistic phenomena, such as translation. Despite the instability of meaning in relation to its underdetermination by reference, it can be a tertium comparationis or “third comparator” for extended human cognition, if gauged through invariants that exist in transfer processes such as translation, as all languages and cultures are rooted in pan-human experience, and thus share and express species-specific ontology. Meaning, seen as a cognitive competence, doesn’t stop outside of the body but extends, depends and partners with other agents and the environment. A novel approach to exploring the transfer properties of some constituent items of the original natural semantic metalanguage in English, that is, semantic primitives, is presented: FrameNet’s semantic frames -evoked by the primes SEE and FEEL- were extracted from EuroParl, a parallel corpus that allows for the automatic word alignment of the items with their synonyms. Large Ontology Multilingual Extraction was used. Afterwards, following the Semantic Mirrors Method, a procedure that consists in back-translating into source language, the translatological examination of translated and original versions of the items was performed. A fully automated pipeline was designed and tested, with the purpose of exploring associated frame shifts and to thus begin a research agenda on their alleged universality as linguistic features of translation, which will be complemented with and contrasted against further massive feedback through a citizen science approach, as well as cognitive and neurophysiological examinations. Additionally, an embodied account of frame semantics is proposed.